Non-parenchymal TREM-2 protects the liver from immune-mediated hepatocellular damage. Issue 3 (27th January 2018) - Perugorria, Maria J; Esparza-Baquer, Aitor; Oakley, Fiona; Labiano, Ibone; Korosec, Ana; Jais, Alexander; Mann, Jelena; Tiniakos, Dina; Santos-Laso, Alvaro; Arbelaiz, Ander; Gawish, Riem; Sampedro, Ana; et al.
Abstract : Objective: Liver injury impacts hepatic inflammation in part via Toll-like receptor (TLR) signalling. Triggering receptor expressed on myeloid cells 2 (TREM-2) modulates TLR4-mediated inflammation in bone marrow (BM)-derived macrophages but its function in liver injury is unknown. Here we hypothesised that the anti-inflammatory effects of TREM-2 on TLR signalling may limit hepatic injury. Design: TREM-2 expression was analysed in livers of humans with various forms of liver injury compared with control individuals. Acute and chronic liver injury models were performed in wild type and Trem-2 -/- mice. Primary liver cells from both genotypes of mice were isolated for in vitro experiments. Results: TREM-2 was expressed on non-parenchymal hepatic cells and induced during liver injury in mice and man. Mice lacking TREM-2 exhibited heightened liver damage and inflammation during acute and repetitive carbon tetrachloride and acetaminophen (APAP) intoxication, the latter of which TREM-2 deficiency was remarkably associated with worsened survival. Liver damage in Trem-2 -/- mice following chronic injury and APAP challenge was associated with elevated hepatic lipid peroxidation and macrophage content. BM transplantation experiments and cellular reactive oxygen species assays revealed effects of TREM-2 in the context of chronic injury depended on both immune and resident TREM-2 expression. Consistent with effects of TREM-2 on inflammation-associated injury, primary hepatic macrophages and hepatic stellate cells lacking TREM-2 exhibited augmented TLR4-driven proinflammatory responses. Conclusion: Our data indicate that by acting as a natural brake on inflammation during hepatocellular injury, TREM-2 is a critical regulator of diverse types of hepatotoxic injury.